Convergence of blockchain, AI and IoT a digital platform - Balusamy, Balamurugan; Poongodi, T.; Manu, M. R. ca. 20./21. Jh; Karthikeyan, S. ca. 20./21. Jh; Sharma, Yogesh ca. 20./21. Jh (CRC Press, 2023)
"Convergence of Blockchain, AI and IoT: A Digital Platform discusses the convergence of three powerful technologies that play into the digital revolution and blur the lines between biological, digital, and physical objects. This book covers novel algorithms, solutions for addressing issues in applications, security, authentication, and privacy"--
Literaturangaben
Keywords: Internet der Dinge; Data Science; Blockchain; Peer-to-Peer-Netz; Blockchains (Databases); Internet of things; Artificial intelligence